Edukasi Terkait Pemilahan Sampah di Klinik Kasih Bunda Bantul Pasca Penutupan TPA di Piyungan Bantul - Riskha Dora Candra Dewi; Dhyani Ayu Perwiraningrum (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
This service was carried out to provide education to the people of Bantul after the closure of the Piyungan Bantul TPA. This service was carried out on May 10 2024 at the Kasih Bunda Clinic Hall. This activity involves various groups of residents around the Clinic, starting from young teenagers, adults and the elderly. The activity starts at 09:00 WIB and finishes around 15:00 WIB with several educational materials. The result is that this activity is an effort to educate ourselves through recognizing the type of waste that is closest to us, so that it is easier to reach. From the initial introduction to education on waste management, some participants only just understood the importance of sorting waste because in the beginning they often mixed up the three waste bins. However, others have made several efforts to sort waste, for example between B-3 and other waste